1970
DOI: 10.1084/jem.132.4.636
|View full text |Cite
|
Sign up to set email alerts
|

The Toxoplasma Gondii Oocyst From Cat Feces

Abstract: Toxoplasma infection is c o m m o n in m a n and animals, yet for 60 years the life cycle of Toxoplasma gondii remained unknown. R e c e n t l y a new form of Toxoplasma was found in the feces of cats that had eaten Toxoplasma-infected mice (for review of earlier work see [1]). This fecal form is biologically different from the known stages of Toxoplasma. While searching the feces of cats for a morphological equivalent of Toxoplasma, several candidate forms such as fungi, cysts of flagellates, and coccidian oo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
168
0
19

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 306 publications
(190 citation statements)
references
References 23 publications
3
168
0
19
Order By: Relevance
“…To evaluate the basic mechanics of the T. gondii oocyst wall, we limited the use of chemicals to avoid any modification of the wall structure because of handling or storage conditions. For this, oocysts were sporulated in water rather than in 2% (vol/vol) aqueous sulfuric acid solution, which is commonly used for oocyst sporulation and subsequent storage (11,22,48). After a 5-d sporulation process, the oocyst suspension contained 18.6 ± 2.7% of NS, 18.3 ± 6.4% of SB, and 63.0 ± 5.9% of SP oocysts (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate the basic mechanics of the T. gondii oocyst wall, we limited the use of chemicals to avoid any modification of the wall structure because of handling or storage conditions. For this, oocysts were sporulated in water rather than in 2% (vol/vol) aqueous sulfuric acid solution, which is commonly used for oocyst sporulation and subsequent storage (11,22,48). After a 5-d sporulation process, the oocyst suspension contained 18.6 ± 2.7% of NS, 18.3 ± 6.4% of SB, and 63.0 ± 5.9% of SP oocysts (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A few days postinfection, unsporulated (uninfective) spheroid oocysts (10 × 12 μm) are excreted in cat feces and become rapidly infective following aerobic sporulation (22). Sporulation results in different subpopulations of maturing oocysts during the first few days (22): unsporulated (NS), "sporoblast-staged" (SB), and fully sporulated (SP) oocysts (11,22).…”
mentioning
confidence: 99%
“…At the same time, it is only in the feline host that sexual multiplication of this parasite takes place, so cats serve as the only site wherein genetic recombination and re-assortment of this parasite can occur. For the past several decades, it has been considered that, in spite of sexual recombination, there is only minimal genetic diversity among different isolates of T. gondii from around the world, with isolates being placed mainly in one of three genetic strains, Type I, II, and III [28]. However, it has recently been shown that there is significantly more genetic diversity in isolates from Brazil [29].…”
Section: Diagnosis and Treatment Of Infection In Catsmentioning
confidence: 99%
“…No information yet exists to explain the drivers for this genetic diversity on St Kitts; additionally, no information exists to describe variability on other islands of the archipelago. We are only beginning to unravel the actual genetic relationship between virulence and the genetic makeup of the different strains of T. gondii present in the environment and in cases of human and animal disease [28]. Work on the genetics of virulence has indicated that some rhoptry proteins (held in the rhoptry organelles and released at the time of host cell penetration), for example ROP18, are linked to virulence in different genetic strains irrespective of their genetic strain assortment.…”
Section: Diagnosis and Treatment Of Infection In Catsmentioning
confidence: 99%
“…Contact with cats, in general, was not epidemiologically important, but the presence of young cats was important (p = 0.031), probably because these animals are in age of greater risk of primo-infection by T. gondii and release oocysts into the environment (DUBEY, MILLER, FRENKEL, 1970). Souza et al (1987) studying a rural area, found that the presence of cats in the residences influenced on the parasite transmission, in the same way, in urban areas of Minas Gerais State, Camargo, Antunes and Chiari (1995) showed higher seroprevalence in humans who had contact with cats.…”
Section: Discussionmentioning
confidence: 99%